In silico design of a multi-epitope vaccine against Cryptosporidium parvum using structural and immunoinformatics approaches - Guneswar Sethi; Avinash Kant Lakra; Kirti Nirmal; Jeong Ho Hwang (PLoS ONE, 2025)
Background Cryptosporidium parvum is a waterborne protozoan parasite responsible for diarrheal illness in humans and animals. The lack of effective vaccines and the emergence of antimicrobial resistance underscore the urgent need for novel prophylactic strategies. Methods A structure-based immunoinformatics approach was used to design a multi-epitope subunit vaccine (MESV) targeting immunogenic regions of C. parvum . Three proteins, Cp15, Cp23, and CpP2, were selected based on antigenicity, non-allergenicity, non-homology with host proteins, and absence of transmembrane domains. B-cell, CD4 + , CD8 + , and IFN-γ-inducing epitopes were identified and screened for high antigenicity, non-allergenicity, and non-toxicity. To enhance immune recognition, the lipoprotein LprA, a TLR2 agonist, was fused at the N-terminus using an EAAAK linker, and a PADRE sequence was added to improve helper T-cell responses. Linkers were applied to ensure proper epitope separation and processing. Population coverage was analyzed to evaluate the distribution of HLA-restricted epitopes across global populations. Structural modeling and flexibility analysis (CABS-flex) were performed to assess construct stability. Interactions with TLR2 and TLR4 were examined via molecular docking and 100-ns molecular dynamics (MD) simulations, with MM-GBSA used to estimate binding free energies. Immune simulations predicted host immune responses, while codon optimization, in silico cloning, and mRNA secondary structure prediction assessed expression and transcript stability. Results The MESV showed strong binding to TLR2 (−1328.4 kcal/mol) and TLR4 (−1133.3 kcal/mol), with MD simulations confirming stable complexes. Immune simulations indicated robust antibody production, T-cell activation, cytokine release, and dendritic cell recruitment. The vaccine demonstrated global HLA population coverage of 95.92%, with favorable expression and mRNA folding profiles. Conclusion The MESV construct demonstrated strong immunogenicity, structural stability, and broad population coverage, underscoring its potential as a promising vaccine candidate against C. parvum . Furthermore, experimental validation is warranted to confirm its safety and efficacy.